Waste in the geopolymerization process. Proposal of the use of asbestos and fly ashes in the production of geopolymer concrete - Marta Wójcik (Advances in Mechanical and Materials Engineering, 1970)
Due to the specific physical, chemical and mechanical properties, the worldwide production of geopolymers is increasing systematically. The high mechanical resistance and the low sensitivity to the high temperature result in the application of geopolymers in many sectors of economy, especially in civil engineering. Additionally, the low emission of carbon dioxide caused that geopolymers are often called „green” material. The wide range of the application of geopolymers requires new substances which could be used in their production. From environmental point of view, the use of waste products in the production of geopolymers is the best solution. Due to the content of silica and aluminum, asbestos dust might be successfully used in the synthesis of geopolymers. This article presents the possibility of recycling of asbestos waste and coal fly ashes in the production of geopolymer concrete. The final product of this method might be used in the construction industry without the risk for the environment. The proposed solution enables to utilize the harmful material, i.e. asbestos dust in accordance with the waste hierarchy and sustainable development.